Evidence That Tumor Microenvironment Initiates Epithelial-To-Mesenchymal Transition and Calebin A can Suppress it in Colorectal Cancer Cells - Buhrmann, Constanze; Brockmueller, Aranka; Harsha, Choudhary; Kunnumakkara, Ajaikumar B.; Kubatka, Peter; Aggarwal, Bharat B.; Shakibaei, Mehdi (Frontiers in Pharmacology, 2021)
Background: Tumor microenvironment (TME) has a pivotal impact on tumor progression, and epithelial-mesenchymal transition (EMT) is an extremely crucial initial event in the metastatic process in colorectal cancer (CRC) that is not yet fully understood. Calebin A (an ingredient in Curcuma longa) has been shown to repress CRC tumor growth. However, whether Calebin A is able to abrogate TME-induced EMT in CRC was investigated based on the underlying pathways. Methods: Two CRC cell lines (HCT116, RKO) were treated with Calebin A and/or an FAK inhibitor, cytochalasin D (CD) to investigate the action of Calebin A in TME-induced EMT-related tumor progression. Results: TME induced viability, proliferation, and increased invasiveness in 3D- alginate CRC cultures. In addition, TME stimulated stabilization of the master EMT-related transcription factor (Slug), which was accompanied by changes in the expression patterns of EMT-associated biomarkers. Moreover, TME resulted in stimulation of NF-kB, TGF-β1, and FAK signaling pathways. However, these effects were dramatically reduced by Calebin A, comparable to FAK inhibitor or CD. Finally, TME induced a functional association between NF-kB and Slug, suggesting that a synergistic interaction between the two transcription factors is required for initiation of EMT and tumor cell invasion, whereas Calebin A strongly inhibited this binding and subsequent CRC cell migration. Conclusion: We propose for the first time that Calebin A modulates TME-induced EMT in CRC cells, at least partially through the NF-kB/Slug axis, TGF-β1, and FAK signaling. Thus, Calebin A appears to be a potential agent for the prevention and management of CRC.